Mortality and risk factors for ruptured abdominal aortic aneurysm after repair endovascular (rARE) - Melissa Jones, MSc, MD; Peter Faris, PhD; Randy Moore, MD, FRCSC, FACS (Journal of Vascular Surgery Cases and Innovative Techniques, 2023)
Objective: The aim of this study was to characterize risk factors for infrarenal abdominal aortic aneurysm rupture after endovascular repair (rARE) and evaluate 30-day mortality in comparison to primary ruptured abdominal aortic aneurysm (rAAA). Methods: A retrospective review of all adult patients with rAAA at a single tertiary university care center between February 11, 2006, and December 31, 2018, was performed. A total of 267 patients with rAAA were identified, 11 of whom had rARE. Descriptive statistics were applied due to the small sample size. Results: Overall 30-day mortality was similar between primary rAAA and rARE (31.5% vs 27.3%); however, patients with rARE were more likely to receive palliative care (3.9% vs 18.2%). Mortality of patients who underwent operative intervention was 11.1% for rARE and 28.7% for primary rAAA at 30 days. All patients had an endoleak at the time of rupture. Type 1 and type 3 endoleaks resulting in direct aortic sac pressurization were the primary cause of rARE (9 of 11 patients); however, rupture occurred in two patients with only a type 2 endoleak. There was no sac expansion at the time of rupture in four of 11 patients with rARE. Four of 11 patients were lost to follow-up prior to rARE. Conclusions: rARE is an uncommon complication following EVAR and contributes to late aneurysm-related mortality following endovascular repair. Although the 30-day mortality rate was similar for rARE and primary rAAA, larger series are required to determine which patients with rARE will benefit from intervention. The presence of endoleak and sac expansion may alert surgeons to increased risk of rARE; however, a subset of patients with rARE did not have sac expansion or surveillance imaging on follow-up. Loss to lifelong imaging surveillance remains a risk factor for rARE.